2014
DOI: 10.1186/1471-2458-14-90
|View full text |Cite
|
Sign up to set email alerts
|

Timeliness of childhood vaccine uptake among children attending a tertiary health service facility-based immunisation clinic in Ghana

Abstract: BackgroundChildhood immunisation is a cost-effective activity in health. Immunisation of children has contributed to reducing child morbidity and mortality. In the last two decades, global deaths from vaccine-preventable illnesses have decreased significantly as a result of immunisation. Similar trends have been observed in Ghana following the introduction of the Expanded Programme on Immunisation. The administration of vaccines is based on the period of highest susceptibility among others. Ghana has long used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
30
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 15 publications
8
30
2
Order By: Relevance
“…However, the proportion of on-time vaccination for BCG and measles were 88.9% and 50.5%, which were comparatively lower as compared to our study. (12) Another study conducted by Holambe VM et al at a tertiary care center of Maharashtra, 66% of the babies presented on time for vaccination, which was similar to our study. (17) In our study, delayed vaccination was more when the age of the mothers were less than 30 years, i.e.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…However, the proportion of on-time vaccination for BCG and measles were 88.9% and 50.5%, which were comparatively lower as compared to our study. (12) Another study conducted by Holambe VM et al at a tertiary care center of Maharashtra, 66% of the babies presented on time for vaccination, which was similar to our study. (17) In our study, delayed vaccination was more when the age of the mothers were less than 30 years, i.e.…”
Section: Discussionsupporting
confidence: 81%
“…(12), (13) {Formula n = deff * Np (1-p)/ [d 2 /1.96 *(N-1) +p(1-p)] n= sample size deff = design effect = 1 N = population size = 2500 P = prevalence = 0.873 d= desired precision= 5%}…”
Section: Methodsmentioning
confidence: 99%
“…However, there are also substantial knowledge gaps regarding the benefits of the practice and poor adherence to recommended vaccine schedules, especially beyond the neonatal period. Timeliness of vaccine uptake has been associated with hospital delivery [28], a time when the initial vaccines are given, and, in general, vaccination schedule adherence tends to decrease subsequently with later vaccines [21][22][23] as was found to be the case in our study. Common sources of vaccination awareness were the hospitals/ clinics or the media (radio and television stations) or community announcements with a Public Address System.…”
Section: Discussionsupporting
confidence: 72%
“…Various studies have identified that adherence to vaccine schedules tend to be highest at birth for hospital deliveries, but subsequently fall due to various factors, including low levels of knowledge of vaccine specific schedules and gaps between awareness and adherence to vaccine schedules [21][22][23]. Due to suboptimal vaccination rates, we aimed to evaluate current knowledge, attitudes, and practices of parents and caregivers of children between 1 month and 5 years old in the Barekese subdistrict of Ghana regarding immunizations; through a mixed quantitative-qualitative survey as part of the Barekuma Community Collaborative Development Programme (BCCDP) [24].…”
Section: Open Accessmentioning
confidence: 99%
“…Paid maternity leave -defined as "leave that the country guarantees employed women in connection with the birth of a child" -can provide households with the opportunity to vaccinate their children without requiring a tradeoff between providing health care for infants and earning income (Daku et al, 2012). Insufficient paid maternity leave, thus, may contribute to low or delayed vaccination uptake among children (Laryea et al, 2014).…”
Section: Introductionmentioning
confidence: 99%